2005
DOI: 10.1002/jctb.1261
|View full text |Cite
|
Sign up to set email alerts
|

Acidogenic fermentation of blended food‐waste in combination with primary sludge for the production of volatile fatty acids

Abstract: The performance of a laboratory-scale anaerobic acidogenic fermenter fed with a mixture of blended kitchen food-waste and primary sludge from a sewage treatment plant was investigated for the production of volatile fatty acids (VFA). The operating variables for acidogenic fermentation were kitchen food-waste content (10 and 25 wt %), hydraulic retention time (HRT: 1, 3 and 5 days), temperature (ambient: 18 ± 2• C, and mesophilic: 35 ± 2 • C) and pH (varied from 5.2 to 6.7). The experimental results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…3 Variations of total SCFAs concentration at different pH Leiyu FENG et al Co-fermentation of WAS with food waste for short-chain fatty acids production participation of SCFAs consumers, such as methanogen. In the literature, almost the same results were found by Min et al during the acidogenic fermentation of food waste in combination with primary sludge for the production of volatile fatty acids [8]. They found a decrease of 2610 mg COD$L -1 for SCFAs when hydraulic retention time was more than 10 d, which was attributed to the possible conversion of SCFAs into biogas of methane and carbon dioxide.…”
Section: Scfas Productionsupporting
confidence: 51%
See 2 more Smart Citations
“…3 Variations of total SCFAs concentration at different pH Leiyu FENG et al Co-fermentation of WAS with food waste for short-chain fatty acids production participation of SCFAs consumers, such as methanogen. In the literature, almost the same results were found by Min et al during the acidogenic fermentation of food waste in combination with primary sludge for the production of volatile fatty acids [8]. They found a decrease of 2610 mg COD$L -1 for SCFAs when hydraulic retention time was more than 10 d, which was attributed to the possible conversion of SCFAs into biogas of methane and carbon dioxide.…”
Section: Scfas Productionsupporting
confidence: 51%
“…Additional advantages include the increased digestion rate and hygienic solubilization. Min et al reported the study of acidogenic fermentation of blended food-waste in combination with primary sludge for SCFAs production and found that the concentration of effluent SCFAs and its production rates were higher at ambient temperature than those at mesophilic one [8]. Ağdağ and Sponza presented the effect of co-disposal of industrial sludge with the organic fraction of municipal solid wastes (OFMSW) on anaerobic treatment of domestic solid waste and the leachate characteristics [12,13], showing that co-digestion of industrial sludge and OFMSW had a positive effect related to COD and SCFAs production and a synergistic effect between municipal solid wastes (MSW) and industrial sludge driven the degradation of organic matter.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…blending) has a greater solids content than traditional wastewater digester feedstock, at 15% or higher (Li et al, 2011). Food waste also has a much higher COD (Min et al, 2005), which indicates a greater potential for producing methane (Droste, 1996). Anaerobic digestion of solid waste of all sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…blending) has greater solids content than traditional wastewater digester feedstock at 15% or higher (Li et al, 2010). Food waste also has a much higher COD (Min et al, 2005), which indicates a greater potential for producing methane (Droste, 1996). Anaerobic digestion of solid waste of all sources (e.g.…”
Section: Introductionmentioning
confidence: 99%